Glycyrrhizin Attenuates Toll Like Receptor-2, -4 and Experimental Vasospasm in a Rat Model. (23rd July 2014) - Chang, Chih-Zen; Wu, Shu-Chuan; Kwan, Aij-Lie
Abstract : Upregulated TLRs are observed in the serum of animals following experimental subarachnoid hemorrhage. This study was to examine glycyrrhizin's effect on proinflammatory cytokines and TLRs in SAH rats. Administration with glycyrrhizin was initiated 24 hr before and 1 hr later using osmotic minipump. Basilar arteries were harvested to examine TLRs mRNA and protein (rt-PCR and western blot) and CSF cytokines (rt-PCR). Morphologically, deformed endothelium, tortuous elastic lamina, and smooth muscle necrosis were observed in the SAH rats, but were absent in the glycyrrhizin pretreatment group. The TLR-3 protein level was not increased in SAH animals, compared with the controls, while that of TLR-2 and -4 in the SAH only and SAH plus vehicle groups was significantly elevated (P < 0.01 ). Pretreatment and treatment with glycyrrhizin reduced TLR-2 and -4 by 28 ± 8 % and 33.4 ± 9.2 %, respectively. Likewise, glycyrrhizin was able to reduce the IL-1 β and MCP-1 mRNA levels. This study shows glycyrrhizin exerts anti-inflammatory effects on SAH induced vasospasm and attenuates the ultrashort time expression of TLRs, like TLR-2 and -4. It corresponds to SAH induced early brain injury. These findings offer credit to the antivasospastic effect of glycyrrhizin and its effect on SAH induced early brain injury.